Costly investment, complementarities, international technological-knowledge diffusion and the skill premium - Afonso, Óscar (2010)
We examine the behaviour of the skill premium in a two-country general equilibrium growth model assuming (i) technological-knowledge diffusion; (ii) internal costly investment in both physical capital and R&D; and (iii) complementarities between intermediate goods in production. We find that these three economic features affect the steady-state growth rate in both countries. However, only in the imitator country do they influence the skill premium. We also find that the steady-state skill premium in the innovator country is affected by its relative labor productivity rather than by its relative labor endowments. This result contrasts with most skill-biased technological change models and suggests that the sustained increase in the skill premium observed in several developed countries over the last three decades may have been due to increases in the relative productive advantage of skilled labor.